2021
DOI: 10.1002/clt2.12013
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of self‐reported rhinitis, conjunctivitis, and asthma predicts IgE sensitization in more than 25,000 Danes

Abstract: Background Allergic rhinitis (AR), allergic conjunctivitis (AC), and asthma composing multiple phenotypes and improved understanding of these phenotypes and their respective risk factors are needed. Objectives The objective of this study was to define the prevalence of AR, AC, and asthma and their association with allergen‐specific immunoglobulin E (sIgE) sensitization in a large cohort of blood donors and identify risk factors. Methods From the nationwide population‐based Danish Blood Donor Study, 52,976 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“… 10 In these studies, the age range was wider (16–75 years), and the definition of AD was different from the definition used in our study. Risk factors for AR, AC, and asthma were studied in adults; in a Danish study ( n = 52,976), upbringing on a farm with livestock compared to other levels of urbanization had a protective effect on allergic rhino‐conjunctivitis, 1 which was also seen in the current study. The protective effect of farm upbringing on the triad of AD, asthma, and AR or their different combinations was not confirmed in another setup.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“… 10 In these studies, the age range was wider (16–75 years), and the definition of AD was different from the definition used in our study. Risk factors for AR, AC, and asthma were studied in adults; in a Danish study ( n = 52,976), upbringing on a farm with livestock compared to other levels of urbanization had a protective effect on allergic rhino‐conjunctivitis, 1 which was also seen in the current study. The protective effect of farm upbringing on the triad of AD, asthma, and AR or their different combinations was not confirmed in another setup.…”
Section: Discussionsupporting
confidence: 66%
“…Corresponding findings were reported in a recent Danish study ( n = 52,976), in which sensitization to common inhalant allergens was a risk factor for AR, AC, and asthma. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the participants, 90% were smokers or former smokers. Smoking has been mentioned as a risk factor for developing occupational asthma among crab processing workers ( 28 ), but a new, large Danish study have indicated that smoking is a protective factor in having asthma ( 29 ). In the present study, the number of never smokers was so small that it did not make sense to examine possible differences in the risk of asthma between smokers and never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The second self-reported manifestation of allergy among healthy Danish donors was AC (15%). 16 The frequency of ocular symptoms was higher in girls than in boys, except in vernal keratoconjunctivitis (VKC). Genetic, hormonal, and cosmetic factors are being investigated as possible causes.…”
Section: Epidemiologymentioning
confidence: 99%